Strategic Management of Pesantren Organisational Resilience in a Plural Society Through Multicultural Islamic Education - Ali Wafa; Maskuri Maskuri; M. Mas’ud Said (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to explore the role of strategic management in enhancing the organizational resilience of Pesantren Miftahul Qulub, an Islamic boarding school operating in a socially and religiously plural environment. Using a qualitative, ethnographic approach, data were gathered through in-depth interviews, participant observation, and document analysis. The research reveals that the pesantren’s resilience is not solely rooted in religious tradition or charismatic leadership but is significantly influenced by strategic management practices. These include continuous internal and external environmental analysis, the institutionalization of multicultural Islamic values, and adaptive decision-making that fosters social capital and internal cohesion. Leadership at the pesantren continuously adapts its strategic orientation to the social dynamics of its plural environment, focusing on values like openness, equality, humanism, and local wisdom. By embedding these values into daily governance and operations, the pesantren can sustain public legitimacy, strengthen relationships with diverse stakeholders, and navigate the challenges of social and religious diversity. The novelty of this research lies in its integrated model that links strategic management, multicultural Islamic commitments, and organizational resilience in plural societies. Unlike previous studies that treat these concepts in isolation, this study demonstrates their co-evolution within pesantren governance. The findings highlight the importance of three interconnected governance practices: systematic environmental scanning, institutionalization of multicultural values, and resilience-building through routines that maintain legitimacy and cohesion. This framework not only provides practical guidance for pesantren leaders but also contributes to comparative research on religious organizations in diverse settings, emphasizing the transferability of these findings to other contexts.